2022
DOI: 10.1177/21676968221121590
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Investigation of the Positive and Negative Impacts of the COVID-19 Pandemic on Post-Secondary Students’ Mental Health and Well-Being

Abstract: Evidence suggests that post-secondary students without pre-existing mental health concerns may have experienced worsening mental health during the COVID-19 pandemic, relative to students with pre-existing mental health concerns. To clarify the psychological impacts of the pandemic, and elucidate why differences may exist among students, 20 interviews were conducted with emerging adults enrolled in university. Using directed content analysis, eight themes were identified: three more common among students with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…The alumni’s perception of isolation during the pandemic is in accordance with a study of students in general. In that study, all students experienced stressors during the pandemic, and those without pre-existing mental health concerns reported greater increases in social and academic isolation, relative to students with pre-existing mental health concerns [ 16 ]. During the pandemic, the use of various pedagogic techniques was limited and reduced to online lectures.…”
Section: Discussionmentioning
confidence: 99%
“…The alumni’s perception of isolation during the pandemic is in accordance with a study of students in general. In that study, all students experienced stressors during the pandemic, and those without pre-existing mental health concerns reported greater increases in social and academic isolation, relative to students with pre-existing mental health concerns [ 16 ]. During the pandemic, the use of various pedagogic techniques was limited and reduced to online lectures.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health concerns have escalated with the persistence of the COVID-19 pandemic, affecting all pro les of post-secondary students. In a recent qualitative study, students without pre-existing mental health conditions reported more frequent social and academic isolation than those with pre-existing mental health concerns (19). Furthermore, a recent meta-analysis noted an increase in the prevalence of anxiety (36%) and depression (39%) during the pandemic (20).…”
Section: Introductionmentioning
confidence: 98%
“…Mental health concerns were exacerbated by the COVID-19 pandemic, affecting all profiles of post-secondary students [ 18 ]. In a recent qualitative study, students without pre-existing mental health conditions reported greater social and academic isolation than those with pre-existing mental health concerns [ 19 ]. Furthermore, a recent meta-analysis noted an increase in the prevalence of anxiety (36%) and depression (39%) during the pandemic [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These strains are worsened in smaller institutions with fewer staff and resources [17]. Treatment barriers and service use amid the COVID- 19 pandemic have yet to be fully delineated.…”
Section: Introductionmentioning
confidence: 99%